2022
DOI: 10.1108/jiabr-03-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

Related party disclosures in financial reporting for Islamic banks

Abstract: Purpose The purpose of this study is to determine the impacts of related party transactions on the performance of Islamic banks in Pakistan. In addition, this study aims to determine whether corporate governance mechanisms enhance company performance and mitigate agency problems associated with related party transactions in the Islamic banks. Design/methodology/approach Sample includes all Islamic banks domiciled in Pakistan from 2017 to 2021. To run the regression models, the regression assumptions about no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In the following, a discussion of the hypotheses that have been tested previously will be presented. From the simple regression test, the results showed that the influence of Understanding Accounting on the Decision to Conduct Online Transactions for the Department of Commerce at the Lhokseumawe State Polytechnic for students of Islamic Institution Accounting was 1.348 (Rafay, 2016). This means that if the Understanding of Muamalah Maaliyaah Contracts increases by one unit, then the Decision to Conduct Muamalah Transactions Online increases by 1.348 assuming the other independent variables are of a fixed value (Syaichoni & Setiawan, 2022).…”
Section: Coefficient Of Determination (R2)mentioning
confidence: 99%
“…In the following, a discussion of the hypotheses that have been tested previously will be presented. From the simple regression test, the results showed that the influence of Understanding Accounting on the Decision to Conduct Online Transactions for the Department of Commerce at the Lhokseumawe State Polytechnic for students of Islamic Institution Accounting was 1.348 (Rafay, 2016). This means that if the Understanding of Muamalah Maaliyaah Contracts increases by one unit, then the Decision to Conduct Muamalah Transactions Online increases by 1.348 assuming the other independent variables are of a fixed value (Syaichoni & Setiawan, 2022).…”
Section: Coefficient Of Determination (R2)mentioning
confidence: 99%
“…Bhuiyan and Roudaki (2018) in News land found that half of the failed firms were involved in RPTs and later convicted of financial statement fraud. In Pakistan, Rafay (2022) found that related party borrowings indicate expropriation and conflict of interest, whereas related party revenues indicate propping and efficient transactions. Further, Amidu et al, (2019) in Ghana found that firms engaged in some of transfer pricing strategies and financial statement fraud did so to avoid tax.…”
Section: Related Party Transactions and Financial Statement Manipulationmentioning
confidence: 99%